Reliability of Rehabilitative Ultrasound Imaging In Measuring Thickness of Levator Scapula Muscle in Asymptomatic Women - Bokaee, Fateme; Rezasoltani, Asghar; Dehghan Manshadi, Farideh; Naimi, Sedighh Sadat; Etemadi, Fateme; Akbarzadeh Baghban, Alireza; Azimi, Hadi (Journal of Clinical Physiotherapy Research, 2016)
Introduction: Levator Scapula Muscle (LSM) is one of the stabilizers of the scapulae. Shortening of this muscle disrupts shoulder biomechanics and results in shoulder pain. Rehabilitative Ultrasound imaging (RUSI) has been introduced as a non-invasive method to measure muscle thickness. The present study aimed to determine the intra-rater reliability of RUSI to measure thickness of LSM in a group of asymptomatic women. Materials and method: Images of LSM were taken using RUSI at the level of the forth cervical vertebra in sitting position in 20 asymptomatic women aged 20-36 years. Images were obtained by one examiner on two separate days and muscle thickness was measured using RUSI. Intraclass Correlation Coefficients (ICC), Standard Error of Measurement (SEM), Smallest Detectable Difference (SDD), and Bland-Altman plot were used for the assessment of reliability. Results: The results of ICC (0.9), SEM (0.26 mm), and SDD (0.72 mm) values revealed an excellent intra-rater reliability and accuracy of RUSI to measure LSM thickness in asymptomatic women. Conclusion: The method of RUSI used in the current study is recommended to measure LSM thickness. It can be used to measure thickness of LSM in patients with shoulder pain where the thickness of the muscle varies according to the level of pain and spasm. Keywords: Levator Scapula; Ultrasonography; Muscle; Reliability; Shoulder